Special polyethylene isolation preservative film for rubber tire and preparation method of special polyethylene isolation preservative film

By introducing nanotitanium dioxide and specific copolymers into the polyethylene isolation film, combined with three-layer coextrusion blown film technology, a special polyethylene isolation plastic wrap for rubber tires with excellent UV resistance and self-repair performance was prepared, which solved the shortcomings of existing film materials in UV resistance and self-repair performance and significantly extended the service life of the tire.

CN119820899AActive Publication Date: 2025-04-15HAOCHEN WUXI PLASTIC IND CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510015434.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing polyethylene isolation film has shortcomings in its UV resistance and self-repair properties, which is difficult to meet the protection and maintenance needs of rubber tires during use.

Method used

By introducing nanotitanium dioxide, gamma-(2,3-epoxypropoxy)propyltrimethoxysilane and specific copolymers, such as chlorinated polyethylene, into the polyethylene barrier film, a modified polyethylene material is formed, and an isolation plastic wrap with excellent UV resistance and self-healing properties is prepared by three-layer coextrusion blown film technology.

Benefits of technology

The UV resistance and self-repair performance of polyethylene isolation film are achieved significantly improved, extending the service life of the tire, reducing the frequency of maintenance and replacement, and improving the safety and reliability of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820899A_ABST
    Figure CN119820899A_ABST
Patent Text Reader

Abstract

The invention discloses a special polyethylene isolation preservative film for a rubber tire and a preparation method of the special polyethylene isolation preservative film, belongs to the technical field of rubber tire manufacturing, and is used for solving the technical problems of poor self-repairing performance and ultraviolet resistance of a polyethylene isolation preservative film in the prior art. The preparation method of the special polyethylene isolation preservative film for the rubber tire comprises the following steps: carrying out a reaction on epoxy modified nano titanium dioxide and AABA grafted 2-(2, 4-dihydroxyphenyl)-2H-benzotriazole to obtain modified nano titanium dioxide; reacting lipoic acid with the modified nano titanium dioxide to obtain an intermediate I; in an argon atmosphere, uniformly mixing the intermediate I, chlorinated polyethylene, N, N-dimethylformamide and potassium carbonate, heating for reaction, filtering, washing and drying to obtain modified polyethylene; the polyethylene isolation preservative film prepared by the preparation method disclosed by the invention not only has good wear resistance and ultraviolet resistance, but also has a certain self-repairing function, so that the service life of the film is prolonged, and the cost of a tire is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber tire manufacturing, and in particular to a polyethylene isolation cling film special for rubber tires and a preparation method thereof. Background Art

[0002] In the preparation process of all-steel radial tires and semi-steel radial tires, after natural rubber is refined with various chemical raw materials, it must be isolated from air and sunlight to prevent the oxide layer on the rubber surface from affecting the service life of the tire. People usually use isolation films to bond with rubber sheets to play the role of isolation and preservation. Commonly used isolation films are mostly polyethylene (PE), which is a thermoplastic polyolefin. The polyethylene film prepared with it has the advantages of transparency and excellent mechanical properties, and is widely used in the field of industrial packaging.

[0003] Chinese patent CN101775169A discloses a polyethylene isolation film for tire production, which is mixed with low-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, polyethylene (meth) acrylic acid E(M)AA copolymer for membrane, linear low-density polyethylene, plasticizer, oleic acid amide and plastic-type multifunctional processing aid in a mass ratio of (20-30):(18-20):(15-24):(10-15):(12-20):(0.5-1):(0.4-0.7):(3-5). The invention obtains an isolation film with excellent isolation performance, but the anti-ultraviolet performance of the polyethylene isolation film needs to be further enhanced. Chinese patent CN103862767B discloses a polyethylene isolation film for repeated use in tire production and a preparation method thereof, wherein the polyethylene isolation film for repeated use in tire production includes an outer film, an intermediate film and an inner film in a mass ratio of (30-40):(20-40):(30-40), wherein the outer film and the inner film are both mixed with a composition of low-density polyethylene, linear low-density polyethylene and maleic anhydride grafted polyethylene in a mass ratio of (25-60):(25-60):(9-50), and the intermediate film is a nylon non-woven fabric, polyester or polypropylene wire mesh fabric. The three-layer composite polyethylene isolation film obtained by this invention blocks oxygen, but the polyethylene isolation film prepared by this invention does not have certain self-healing properties. In summary, the development of a polyethylene isolation cling film with good self-healing properties and anti-ultraviolet properties has a very broad market value and important practical significance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a polyethylene isolation cling film specially used for rubber tires and a preparation method thereof, which solves the problems of poor self-repairing performance and anti-ultraviolet performance of the polyethylene isolation cling film.

[0005] In order to achieve the above object, the present invention provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0006] Step (1) mixing anhydrous ethanol, nano titanium dioxide and γ-(2,3-epoxypropoxy)propyltrimethoxysilane uniformly, heating, reacting, filtering, washing and drying after the reaction is completed to obtain epoxy-modified nano titanium dioxide;

[0007] Step (2) mixing N,N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, reacting, washing and drying after the reaction is completed to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0008] Step (3) adding epoxy-modified nano titanium dioxide and AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole to anhydrous ethanol, stirring and mixing, reacting, filtering, washing, and drying after the reaction is completed to obtain modified nano titanium dioxide;

[0009] Step (4) adding lipoic acid to acetone, adding modified nano titanium dioxide, stirring, mixing evenly, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain intermediate I;

[0010] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate are uniformly mixed, heated, reacted, filtered, washed and dried to obtain modified polyethylene after the reaction is completed;

[0011] In step (5), the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, and the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200-230°C; the components of each layer are stacked layer by layer on the upper part of the die through the flow channels of the die head to form a co-extruded film; the film is blown, stretched into a film, air-cooled to shape, surface treated, rolled, slit and packaged to obtain a polyethylene isolation cling film specially used for rubber tires.

[0012] Preferably, the method for preparing chlorinated polyethylene comprises the following steps:

[0013] In a closed, anhydrous, oxygen-free, inert gas environment, dimethylvinylchlorosilane and n-hexane are mixed, ethylene is introduced, triethylaluminum is added, and heating is performed to carry out copolymerization reaction. After the reaction is completed, vacuum distillation is performed and drying is performed to obtain chlorinated polyethylene.

[0014] Preferably, the copolymerization reaction is carried out at 40-45° C. and 0.1-0.2 MPa for 30-50 min.

[0015] Preferably, the usage ratio of dimethylvinylchlorosilane, n-hexane, ethylene and triethylaluminum is 1.5-2.5 g:20-40 mL:0.8-1 mol:0.4-0.6 g.

[0016] Preferably, the mass ratio of anhydrous ethanol, nano-titanium dioxide and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is (1400-3000):(80-100):(30-70); the reaction temperature is 55-75° C., and the reaction time is 3-5 h.

[0017] Preferably, the mass ratio of N,N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is (2000-4000):(80-100):(160-280):(14-26):(30-50); the reaction temperature is 10-18°C, and the reaction time is 4-8h.

[0018] Preferably, the mass ratio of epoxy-modified nano-titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol is (40-60):(140-260):(3000-5000); the reaction temperature is 60-80°C, and the reaction time is 2-4h.

[0019] Preferably, the mass ratio of lipoic acid, acetone and modified nano-titanium dioxide is (80-100):(1200-2400):(16-28); the reaction temperature is 90-110° C., and the reaction time is 20-28 h.

[0020] Preferably, the mass ratio of intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate is (200-280):(120-180):(2000-4000):(80-100); the reaction temperature is 55-65°C, and the reaction time is 34-46h.

[0021] Preferably, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and antistatic agent is (40-80):(6-10):(12-24):(8-16):(2-6).

[0022] Preferably, the film blowing machine adopts a single-screw extruder, the extruder body temperature is 160-220°C, the die head temperature is 170-230°C, and the screw speed is 20-45r / min.

[0023] Preferably, the antistatic agent is one or more of fatty amine, sodium lauryl sulfate, and cinnamic acid glyceride.

[0024] Preferably, the blow-up ratio in the film blowing operation is 1-4.

[0025] Preferably, the stretching speed for stretching into a film is 7-21 m / min.

[0026] Preferably, the height of the cooling line in air-cooling setting is 0.4-0.8m.

[0027] Preferably, the mass ratio of the outer layer film, the middle layer film and the inner layer film is (35-55):(20-32):(35-55).

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. In the present invention, nano titanium dioxide has a certain heat resistance, can enhance the thermal stability and mechanical properties of the matrix material, and under ultraviolet light irradiation, nano titanium dioxide can absorb and scatter ultraviolet rays, and after modification of nano silicon dioxide, it can effectively prevent its agglomeration, thereby achieving uniform dispersion and maintaining functional stability, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane as an organic silane, because of its strong silicon oxygen bond, can effectively improve thermal stability. In the present invention, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole is added to expand the absorption range of ultraviolet rays, with higher absorption efficiency, improve anti-ultraviolet performance, and slow down aging. The acetoacetyl group (-COCH2CO-) in acetoacetyl-o-carboxyaniline is a strong conjugated group with a strong electron-withdrawing effect. It is conjugated with the aromatic ring of the aniline group to enhance the absorption of ultraviolet light by the molecule, especially in the ultraviolet A (UVA) and ultraviolet B (UVB) spectral ranges. This conjugated effect makes acetoacetyl-o-carboxyaniline have stronger anti-ultraviolet properties under ultraviolet irradiation. The hydroxyl group in 2-(2,4-dihydroxyphenyl)-2H-benzotriazole reacts with the carboxyl group in acetoacetyl-o-carboxyaniline to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole; the amino group in AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole reacts with the epoxy group in epoxy-modified titanium dioxide to obtain modified nano-titanium dioxide with tertiary amine groups; adding it to the matrix material can increase its heat resistance and anti-ultraviolet properties and have good compatibility with the matrix material.

[0030] 2. In the present invention, the chlorinated polyethylene obtained by copolymerization of dimethylvinyl chlorosilane and ethylene has better heat resistance than polyethylene; the tertiary amine group in the modified nano titanium dioxide can form an ionic bond with the carboxyl group in thioctic acid, thereby improving the stability of thioctic acid; the hydroxyl group of the formed intermediate I can react with the chlorine group in the chlorinated polyethylene to generate a more heat-resistant and water-resistant ether group, thereby enhancing the crosslinking degree and stability of the polymer, increasing the compatibility of the intermediate I with the chlorinated polyethylene, and further improving its UV resistance and self-repairing properties; the intermediate I contains hydrogen bonds, disulfide bonds, and ionic bonds composed of carboxyl groups and tertiary amine groups for crosslinking, thereby providing the matrix material with excellent mechanical properties; wherein the dynamic disulfide bonds, dynamic hydrogen bonds, and ionic bonds in thioctic acid give the matrix material a certain degree of self-repairing properties, and the tertiary amine group in the modified nano titanium dioxide can form an ionic bond with the carboxyl group in thioctic acid that can aggregate over time or under the action of heating, thereby enhancing the performance of the polymer after repair.

[0031] 3. In the present invention, the polyethylene isolation cling film for rubber tires, which is composed of inner and outer layer films prepared from modified polyethylene and linear low-density polyethylene, high-density polyethylene, polyethylene wax and antistatic agent, and the middle layer film prepared from linear low-density polyethylene, has good barrier properties, stability, UV resistance, tensile properties and certain self-repairing properties. It does not need to be replaced immediately when encountering slight damage, thereby increasing the service life. For application in tires, the self-repairing function can reduce the frequency of maintenance and replacement, reduce overall costs, protect the tire surface, and maintain the freshness of the tire surface. The application of self-repairing technology in tire materials can enhance the safety and reliability of tires during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart of the preparation process of the polyethylene isolation cling film for rubber tires;

[0033] Figure 2 is a process flow chart of the preparation of modified polyethylene in the present invention;

[0034] Figure 3 A schematic diagram of the reaction of preparing AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole from acetoacetyl o-carboxyaniline and 2-(2,4-dihydroxyphenyl)-2H-benzotriazole in the present invention;

[0035] Figure 4 The schematic diagram of the reaction of preparing modified nano titanium dioxide by epoxy-modified nano titanium dioxide and AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole in the present invention;

[0036] Figure 5 It is a bar graph of the anti-ultraviolet performance test results of Examples 1-5 and Comparative Examples 1-3 of the present invention;

[0037] Figure 6 It is a bar graph of the repair test of Example 1 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0041] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are mixed uniformly in a mass ratio of 1400:80:30, reacted at 55° C. for 5 h, filtered after the reaction is completed, washed with deionized water, and dried at 60° C. for 6 h to obtain epoxy-modified nano titanium dioxide;

[0042] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 2000:80:160:14:30, reacted at 10° C. for 8 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 30° C. for 4 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0043] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 40:140:3000, stirred at a speed of 120 r / min for 18 min, reacted at a temperature of 60° C. for 4 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 80° C. for 5 h to obtain modified nano titanium dioxide;

[0044] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 80:1200:16, stirring at a speed of 100 r / min for 20 min, reacting at a temperature of 90° C. for 28 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0045] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate were mixed uniformly in a mass ratio of 200:120:2000:80, reacted at 55°C for 46 hours, filtered, washed with deionized water, and dried at 40°C for 4.5 hours to obtain modified polyethylene;

[0046] Step (5) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200°C; a single-screw extruder is used, the extruder body temperature is 160°C, the die head temperature is 170°C, the screw speed is 45r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 1 and stretched into a film at a stretching speed of 7m / min; air cooling is used for shaping, and the cooling line height is 0.4m; the surface of the cooled film is corona treated, the treatment current is 150A, the maximum output power is 12kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0047] Wherein, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 40:6:12:8:2;

[0048] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 35:20:35.

[0049] Example 2

[0050] This embodiment provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0051] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are mixed uniformly in a mass ratio of 1800:85:40, reacted at 60° C. for 4.5 hours, filtered after the reaction is completed, washed with deionized water, and dried at 65° C. for 5.5 hours to obtain epoxy-modified nano titanium dioxide;

[0052] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 2500:85:190:17:35, reacted at 12° C. for 7 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 35° C. for 3.5 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0053] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 45:170:3500, stirred at a speed of 135 r / min for 16 min, reacted at a temperature of 65° C. for 3.5 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 85° C. for 4.5 h to obtain modified nano titanium dioxide;

[0054] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 85:1500:19, stirring at a speed of 115 r / min for 18 min, reacting at a temperature of 95° C. for 26 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0055] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate were mixed uniformly in a mass ratio of 220:135:2500:85, reacted at 57°C for 43 hours, filtered, washed with deionized water, and dried at 45°C for 4 hours to obtain modified polyethylene;

[0056] Step (5) The outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, and the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 207°C; a single-screw extruder is used, the extruder body temperature is 175°C, the die head temperature is 185°C, the screw speed is 39r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 1 and stretched into a film at a stretching speed of 11m / min; air cooling is used for shaping, and the cooling line height is 0.5m; the surface of the cooled film is corona treated, the treatment current is 160A, the maximum output power is 14kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0057] Wherein, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 50:7:15:10:3;

[0058] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 40:23:40.

[0059] Example 3

[0060] This embodiment provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0061] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are mixed uniformly in a mass ratio of 2200:90:50, reacted at 65° C. for 4 h, filtered after the reaction is completed, washed with deionized water, and dried at 70° C. for 5 h to obtain epoxy-modified nano titanium dioxide;

[0062] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 3000:90:220:20:40, reacted at 14° C. for 6 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 40° C. for 3 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0063] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 50:200:4000, stirred at a speed of 150 r / min for 14 min, reacted at a temperature of 70° C. for 3 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 90° C. for 4 h to obtain modified nano titanium dioxide;

[0064] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 90:1800:22, stirring at a speed of 130 r / min for 16 min, reacting at a temperature of 100° C. for 24 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0065] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate were mixed uniformly in a mass ratio of 240:150:3000:90, reacted at 60°C for 40 hours, filtered, washed with deionized water, and dried at 50°C for 3.5 hours to obtain modified polyethylene;

[0066] Step (5) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 215°C; a single-screw extruder is used, the extruder body temperature is 190°C, the die head temperature is 200°C, the screw speed is 32r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 2 and stretched into a film at a stretching speed of 14m / min; air cooling is used for shaping, and the cooling line height is 0.6m; the surface of the cooled film is corona treated, the treatment current is 170A, the maximum output power is 16kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0067] Among them, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 60:8:18:12:4;

[0068] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 45:26:45.

[0069] Example 4

[0070] This embodiment provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0071] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are uniformly mixed in a mass ratio of 2600:95:60, reacted at 70° C. for 3.5 hours, filtered after the reaction is completed, washed with deionized water, and dried at 75° C. for 4.5 hours to obtain epoxy-modified nano titanium dioxide;

[0072] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 3500:95:250:23:45, reacted at 16° C. for 5 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 45° C. for 2.5 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0073] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 55:230:4500, stirred at a speed of 165 r / min for 12 min, reacted at a temperature of 75° C. for 2.5 h, and after the reaction is completed, filtered, washed with anhydrous ethanol, and dried at a temperature of 95° C. for 3.5 h to obtain modified nano titanium dioxide;

[0074] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 95:2100:25, stirring at a speed of 145 r / min for 14 min, reacting at a temperature of 105° C. for 22 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0075] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate were mixed uniformly in a mass ratio of 260:165:3500:95, reacted at 63°C for 37 hours, filtered, washed with deionized water, and dried at 55°C for 3 hours to obtain modified polyethylene;

[0076] Step (5) The outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, and the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 223°C; a single-screw extruder is used, the extruder body temperature is 205°C, the die head temperature is 215°C, the screw speed is 26r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 3 and stretched into a film at a stretching speed of 17m / min; air cooling is used for shaping, and the cooling line height is 0.7m; the surface of the cooled film is corona treated, the treatment current is 190A, the maximum output power is 18kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0077] Among them, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 70:9:21:14:5;

[0078] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 50:29:50.

[0079] Example 5

[0080] This embodiment provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0081] Step (1) mixing anhydrous ethanol, nano titanium dioxide and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 3000:100:70, reacting at 75°C for 3h, filtering after the reaction, washing with deionized water, and drying at 80°C for 4h to obtain epoxy-modified nano titanium dioxide;

[0082] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 4000:100:280:26:50, reacted at 18° C. for 4 hours, and after the reaction is completed, washed with anhydrous ethanol, and dried at 50° C. for 2 hours to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0083] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 60:260:5000, stirred at a speed of 180 r / min for 10 min, reacted at a temperature of 80° C. for 2 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 100° C. for 3 h to obtain modified nano titanium dioxide;

[0084] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 100:2400:28, stirring at a speed of 160 r / min for 12 min, reacting at a temperature of 110° C. for 20 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0085] In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate were mixed uniformly in a mass ratio of 280:180:4000:100, reacted at 65°C for 34 hours, filtered, washed with deionized water, and dried at 60°C for 2.5 hours to obtain modified polyethylene;

[0086] Step (5) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 230°C; a single-screw extruder is used, the extruder body temperature is 220°C, the die head temperature is 230°C, the screw speed is 20r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 4 and stretched into a film at a stretching speed of 21m / min; air cooling is used for shaping, and the cooling line height is 0.8m; the surface of the cooled film is corona treated, the treatment current is 200A, the maximum output power is 20kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0087] Among them, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 80:10:24:16:6;

[0088] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 55:32:55.

[0089] Example 6

[0090] This embodiment provides a method for preparing chlorinated polyethylene, comprising the following steps:

[0091] In a closed, anhydrous, oxygen-free inert gas environment, dimethylvinylchlorosilane and n-hexane were mixed, ethylene was introduced, triethylaluminum was added, copolymerization was carried out at 40°C and 0.1MPa for 50min, after the reaction was completed, vacuum distillation was carried out at 0.08Mpa and 55°C for 6h, and drying was carried out at 40°C for 8h to obtain chlorinated polyethylene;

[0092] Wherein, the usage ratio of dimethylvinylchlorosilane, n-hexane, ethylene and triethylaluminum is 1.5g:20mL:0.8mol:0.4g.

[0093] Comparative Example 1

[0094] This comparative example provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0095] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are mixed uniformly in a mass ratio of 1400:80:30, reacted at 55° C. for 5 h, filtered after the reaction is completed, washed with deionized water, and dried at 60° C. for 6 h to obtain epoxy-modified nano titanium dioxide;

[0096] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 2000:80:160:14:30, reacted at 10° C. for 8 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 30° C. for 4 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0097] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 40:140:3000, stirred at a speed of 120 r / min for 18 min, reacted at a temperature of 60° C. for 4 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 80° C. for 5 h to obtain modified nano titanium dioxide;

[0098] Step (4) mixing lipoic acid, acetone and modified nano titanium dioxide in a mass ratio of 80:1200:16, stirring at a speed of 100 r / min for 20 min, reacting at a temperature of 90° C. for 28 h, and filtering after the reaction, washing with anhydrous ethanol, and drying to obtain intermediate I;

[0099] In an argon atmosphere, the intermediate I, polyethylene and N,N-dimethylformamide were physically mixed in a mass ratio of 200:120:2080, washed with deionized water, and dried at 40°C for 4.5h to obtain modified polyethylene;

[0100] Step (5) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200°C; a single-screw extruder is used, the extruder body temperature is 160°C, the die head temperature is 170°C, the screw speed is 45r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 1 and stretched into a film at a stretching speed of 7m / min; air cooling is used for shaping, and the cooling line height is 0.4m; the surface of the cooled film is corona treated, the treatment current is 150A, the maximum output power is 12kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0101] Wherein, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 40:6:12:8:2;

[0102] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 35:20:35.

[0103] Comparative Example 2

[0104] This comparative example provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0105] Step (1) anhydrous ethanol, nano titanium dioxide, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are mixed uniformly in a mass ratio of 1400:80:30, reacted at 55° C. for 5 h, filtered after the reaction is completed, washed with deionized water, and dried at 60° C. for 6 h to obtain epoxy-modified nano titanium dioxide;

[0106] Step (2) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 2000:80:160:14:30, reacted at 10° C. for 8 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 30° C. for 4 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0107] Step (3) epoxy-modified nano titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol are mixed in a mass ratio of 40:140:3000, stirred at a speed of 120 r / min for 18 min, reacted at a temperature of 60° C. for 4 h, filtered after the reaction, washed with anhydrous ethanol, and dried at a temperature of 80° C. for 5 h to obtain modified nano titanium dioxide;

[0108] Step (4) mixing lipoic acid, modified nano titanium dioxide, polyethylene and N,N-dimethylformamide in a mass ratio of 166:34:120:2080, stirring at a speed of 100 r / min for 20 min, washing with deionized water, and drying at a temperature of 40° C. for 4.5 h to obtain modified polyethylene;

[0109] Step (5) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200°C; a single-screw extruder is used, the extruder body temperature is 160°C, the die head temperature is 170°C, the screw speed is 45r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 1 and stretched into a film at a stretching speed of 7m / min; air cooling is used for shaping, and the cooling line height is 0.4m; the surface of the cooled film is corona treated, the treatment current is 150A, the maximum output power is 12kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0110] Wherein, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 40:6:12:8:2;

[0111] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 35:20:35.

[0112] Comparative Example 3

[0113] This comparative example provides a method for preparing a polyethylene isolation cling film for rubber tires, comprising the following steps:

[0114] Step (1) N, N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed in a mass ratio of 2000:80:160:14:30, reacted at 10° C. for 8 h, and after the reaction is completed, washed with anhydrous ethanol, and dried at 30° C. for 4 h to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole;

[0115] Step (2) mixing lipoic acid, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, polyethylene and N,N-dimethylformamide in a mass ratio of 166:26:120:2088, stirring at a speed of 100 r / min for 20 min, washing with deionized water, and drying at a temperature of 40° C. for 4.5 h to obtain modified polyethylene;

[0116] Step (3) the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate; the middle layer film is linear low-density polyethylene, the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200°C; a single-screw extruder is used, the extruder body temperature is 160°C, the die head temperature is 170°C, the screw speed is 45r / min, and the components of each layer are stacked layer by layer on the upper part of the die through each flow channel of the die head to form a co-extruded film; the film is inflated according to a blowing ratio of 1 and stretched into a film at a stretching speed of 7m / min; air cooling is used for shaping, and the cooling line height is 0.4m; the surface of the cooled film is corona treated, the treatment current is 150A, the maximum output power is 12kW, the film is rolled, cut and packaged to obtain a polyethylene isolation cling film for rubber tires with a thickness of 90μm;

[0117] Among them, the mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and sodium dodecyl sulfate in the outer film and the inner film is 40:6:12:8:2;

[0118] Among them, the mass ratio of the outer layer film, the middle layer film and the inner layer film is 35:20:35.

[0119] The chlorinated polyethylene used in Examples 1-5 of the present invention is the chlorinated polyethylene prepared in Example 6.

[0120] In the examples and comparative examples, linear low-density polyethylene (LLDPE) was purchased from Sinopec Yangzi Petrochemical Co., Ltd., with a grade of DFDA-7042, a melt index of 2.2 g / 10 min, and a density of 0.92 g / cm 3 ; High-density polyethylene is from Shandong Guangchuan Plastic Co., Ltd., item number: 2911; polyethylene wax is from Shanghai Zhenlishi Network Technology Co., Ltd., product name: AC-629A; sodium dodecyl sulfonate is from Guangzhou Jishengxiang Chemical Co., Ltd., item number 55442, CAS number: 2386-53-0; nano titanium dioxide is purchased from Xuancheng Jingrui New Materials Co., Ltd., model JR05, with an average particle size of 5nm; acetoacetyl o-carboxyaniline (AABA) is from Shanghai Liming Chemical Co., Ltd., model: 565754, content: 99%; lipoic acid is from Xi'an Xinmengchen Biotechnology Co., Ltd., single product number: 23; others are all commercially available products.

[0121] Corresponding tests were performed on the polyethylene isolation cling film for rubber tires prepared in Examples 1-5 and Comparative Examples 1-3. The test results are as follows:

[0122] (1) Anti-ultraviolet performance test: The test was carried out using a Japanese Shimadzu UV-3600 spectrophotometer. The test referred to the national standard GB / T2680-2021. The specific test results are shown in Table 1.

[0123] Table 1

[0124]

[0125] It can be seen from the test results in Table 1 that the polyethylene isolation cling film for rubber tires corresponding to Examples 1-5 has excellent ultraviolet absorption performance, the added nano titanium dioxide itself has certain ultraviolet absorption performance, the higher its content, the better the dispersion performance, and the more outstanding the ultraviolet absorption performance; the introduced 2-(2,4-dihydroxyphenyl)-2H-benzotriazole also has excellent ultraviolet absorption performance, increases the ultraviolet absorption range, and improves the absorption efficiency. In Example 1, the hydroxyl group contained in the middle I reacts with the chlorine group in the chlorinated polyethylene to generate an ether bond that is more water-resistant and heat-resistant, and its thermal stability is better. At the same time, the compatibility of the middle I with the matrix material is better, which is more conducive to ultraviolet absorption performance. In Comparative Example 1, the middle I and polyethylene are physically mixed, and the dispersibility is not as good as in Example 1, so the ultraviolet resistance of Comparative Example 1 is lower than that of Example 1; in Comparative Example 1, thioctic acid and the tertiary amine group in the modified nano-titanium dioxide form ionic bonds for cross-linking, so that it has excellent mechanical properties, and the dynamic disulfide bonds and ionic bonds contained in the middle I give the matrix material a certain self-repairing ability. Once it is lacking, its anti-ultraviolet performance is naturally reduced due to the reduction of the repair ability, so the anti-ultraviolet performance of Comparative Example 2 is lower than that of Comparative Example 1; Comparative Example 3 lacks nano-titanium dioxide compared to Comparative Example 2, and its anti-ultraviolet performance is naturally reduced.

[0126] (2) Mechanical property test: The mechanical property test of the polyethylene isolation cling film for rubber tires corresponding to Example 1 and Comparative Examples 1-3 was conducted using the test standard of GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; each was tested three times, and the specific test results are shown in Table 2;

[0127] Table 2

[0128]

[0129] As shown in Table 2, the tensile strength of the polyethylene isolation cling film for rubber tires of Example 1 prepared by the present invention is 30.8MPa. In Example 1, the intermediate I is connected to the chlorinated polyethylene through an ether bond, and the thermal stability of the modified polyethylene obtained is further improved, and the nitrogen atoms, oxygen atoms, etc. contained in it are easy to form hydrogen bonds, increase internal crosslinking, and improve tensile strength. On the contrary, the tensile strength is reduced, so the tensile strength of Example 1 is reduced compared with Example 1; Compared with Example 1, Comparative Example 2 lacks thioctic acid and modified nano-titanium dioxide to form ionic bonds for crosslinking, and the internal crosslinking degree is low, and the tensile strength is reduced; Comparative Example 3 lacks inorganic nano-titanium dioxide compared with Comparative Example 2, so the tensile strength of Comparative Example 3 is lower than that of Comparative Example 2.

[0130] (3) Repair performance test: The corresponding polyethylene isolation cling film for rubber tires in Example 1 and Comparative Examples 1-3 was scratched with a razor blade, with a scratch width of 10 μm and the scratches deep into the tinplate substrate. Then, the scratched polyethylene isolation cling film for rubber tires was placed in an oven and self-repaired at 75°C for 24 hours. It was first taken out of the oven and waited for the polyethylene isolation cling film for rubber tires to cool naturally to room temperature. Each group was tested three times, and the repair rate was recorded and the average value was taken. The specific test results are shown in Table 3;

[0131] Table 3

[0132]

[0133] From the test results of Table 3, it can be seen that the repair rate of the polyethylene isolation cling film for rubber tires of Example 1 reached 96.25%. In Example 1, the intermediate I is connected with the chlorinated polyethylene through an ether group, and the compatibility of the two is good, which is conducive to the performance of the intermediate I with repair performance. Once the dispersibility is reduced, its repair performance is reduced, so the repair performance of Comparative Example 1 is lower than that of Example 1; Comparative Example 2 is compared with Comparative Example 1, and thioctic acid will exist in a metastable state. Due to the reverse closed-loop depolymerization, the compatibility of the matrix material is poor, and the tertiary amine group in thioctic acid and modified nano-titanium dioxide does not form an ionic bond, and the repair performance is reduced, so the repair rate value of Comparative Example 2 is lower than the repair rate value in Comparative Example 1; Comparative Example 3 is compared with Comparative Example 2, and the stability and dispersibility of thioctic acid are both reduced compared with Comparative Example 2, which affects the reduction of the repair performance, so the repair performance in Comparative Example 3 is lower than the repair performance in Comparative Example 2.

[0134] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a polyethylene isolation cling film for rubber tires, characterized in that: The following steps are involved: Step (1) mixing anhydrous ethanol, nano titanium dioxide and γ-(2,3-epoxypropoxy)propyltrimethoxysilane uniformly, heating, reacting, filtering, washing and drying after the reaction is completed to obtain epoxy-modified nano titanium dioxide; Step (2) mixing N,N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, reacting, washing and drying after the reaction is completed to obtain AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole; Step (3) adding epoxy-modified nano titanium dioxide and AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole to anhydrous ethanol, stirring and mixing, reacting, filtering, washing, and drying after the reaction is completed to obtain modified nano titanium dioxide; Step (4) adding lipoic acid to acetone, adding modified nano titanium dioxide, stirring, mixing evenly, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain intermediate I; In an argon atmosphere, the intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate are uniformly mixed, heated, reacted, filtered, washed and dried to obtain modified polyethylene after the reaction is completed; In step (5), the outer film and the inner film are a blend of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and an antistatic agent; the middle layer film is linear low-density polyethylene, and the raw materials required for the three-layer film are sent to three extruders of a three-layer co-extrusion film blowing machine and heated and melted at 200-230°C; the components of each layer are stacked layer by layer on the upper part of the die through the flow channels of the die head to form a co-extruded film; the film is blown, stretched into a film, air-cooled to shape, surface treated, rolled, slit and packaged to obtain a polyethylene isolation cling film specially used for rubber tires.

2. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The preparation method of chlorinated polyethylene comprises the following steps: In a closed, anhydrous, oxygen-free, inert gas environment, dimethylvinylchlorosilane and n-hexane are mixed, ethylene is introduced, triethylaluminum is added, and heating is performed to carry out copolymerization reaction. After the reaction is completed, vacuum distillation is performed and drying is performed to obtain chlorinated polyethylene.

3. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 2, characterized in that: The copolymerization reaction is carried out at 40-45°C and 0.1-0.2 MPa for 30-50 min.

4. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of anhydrous ethanol, nano-titanium dioxide and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is (1400-3000):(80-100):(30-70); the reaction temperature is 55-75°C, and the reaction time is 3-5h.

5. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of N,N-dimethylformamide, acetoacetyl o-carboxyaniline, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is (2000-4000):(80-100):(160-280):(14-26):(30-50); the reaction temperature is 10-18°C and the reaction time is 4-8h.

6. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of epoxy-modified nano-titanium dioxide, AABA-grafted 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and anhydrous ethanol is (40-60):(140-260):(3000-5000); the reaction temperature is 60-80°C, and the reaction time is 2-4h.

7. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of lipoic acid, acetone and modified nano titanium dioxide is (80-100):(1200-2400):(16-28); the reaction temperature is 90-110° C., and the reaction time is 20-28 hours.

8. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of intermediate I, chlorinated polyethylene, N,N-dimethylformamide and potassium carbonate is (200-280):(120-180):(2000-4000):(80-100); the reaction temperature is 55-65°C, and the reaction time is 34-46h.

9. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The mass ratio of modified polyethylene, linear low-density polyethylene, high-density polyethylene, polyethylene wax and antistatic agent is (40-80):(6-10):(12-24):(8-16):(2-6).

10. The method for preparing a polyethylene isolation cling film for rubber tires according to claim 1, characterized in that: The film blowing machine adopts a single screw extruder with an extruder body temperature of 160-220°C, a die head temperature of 170-230°C, and a screw speed of 20-45r / min.

Citation Information

Patent Citations

  • Polyethylene recyclable isolation film for tire production

    CN101775169A

  • A polyethylene release film for reuse in tire production and its preparation method

    CN103862767B

  • Preparation of shaped metal particles and their uses

    CN102365127A

  • Modified polyethylene film material and preparation method thereof

    CN103059371A

  • Polyethylene isolating film reusable in tire production and preparation method of polyethylene isolating film

    CN103862768A